Investigation on Three-dimensional viscoelastic nanofluid with Newtonian heating and binary chemical reaction (International Journal of Emerging Trends in Science and Technology, 2017)
This paper investigated the steady three dimensional boundary layer flow of an incompressible viscoelasticnanofluid in the presence of Newtonian heating and chemical reaction. A mathematical formulation hasdesigned for momentum, temperature and nanofluid solid volume profiles. The coupled partial differentialequations are solved using the Nactsheim-Swigert shooting technique with the six order Runge-Kuttaiteration Method. The results for the dimensionless velocity, temperature, and nanofluid solid volumeprofiles are discussed with the help of graphs.